Looking into the Content of the Canadian Occupational Performance Measure (COPM): A Danish Cross-Sectional Study - Anette Enemark Larsen; Sonja Wehberg; Jeanette Reffstrup Christensen (Occupational Therapy International)
Purpose. To examine the content validity of the Danish version of the Canadian Occupational Performance Measure (COPM-DK). Materials and Methods. This cross-sectional study was performed in a hospital and a community rehabilitation centre. The content validity of the COPM was assessed by relating the clients’ prioritized occupational performance issues (OPIs) to the conceptual model of the Canadian Model of Occupational Performance and Engagement (CMOP-E) and the levels of the Taxonomic Code of Occupational Performance (TCOP). Six occupational therapy lecturers participated in classifying the OPIs using the TCOP. Results. A total of 112 clients from a regional and community-based rehabilitation participated. The 56% regional participants came from a hospital’s hand and knee surgery department. The remaining 44% participants came from a community-based rehabilitation centre with in- and outpatient departments. There were 44% males, with a mean age of 65.2 years. They prioritized 495 OPIs, of which 40% concerned self-care, 32% productivity, and 28% leisure. The prioritized OPIs were divided into a total of 224 different OPIs. There were significant differences in which areas were prioritized in the various population groups. Of the OPIs, 64.3% could be classified into the TCOP levels of occupation and activity, i.e., 1/3 of the OPIs were related to tasks and actions, and thus beyond the scope of the COPM. The interrater agreement of the OPI classification was only fair (kappa 0.3). Conclusion. The content validity of the COPM seems to depend on how and with which clients it is administered. Caution must be taken to secure OPIs on the higher levels of the TCOP, while maintaining the clients’ right to nominate OPI preferences. Therefore, an introductory course and on-going support are recommendable. Bearing this in mind, the COPM seems useful to identify individual clients’ prioritized OPIs in a Danish context.